Does framing of cancer survival affect perceived value of care? A willingness-to-pay survey of US residents. (August 2013) - Lin, Pei-Jung; Concannon, Thomas W; Greenberg, Dan; Cohen, Joshua T; Rossi, Gregory; Hille, Jeffrey; Auerbach, Hannah R; Fang, Chi-Hui; Nadler, Eric S; Neumann, Peter J
Aims : To investigate the relationship between the framing of survival gains and the perceived value of cancer care.Methods : Through a population-based survey of 2040 US adults, respondents were randomized to one of the two sets of hypothetical scenarios, each of which described the survival benefit for a new treatment as either an increase in median survival time (median survival), or an increase in the probability of survival for a given length of time (landmark survival). Each respondent was presented with two randomly selected scenarios with different prognosis and survival improvements, and asked about their willingness to pay (WTP) for the new treatments.Results : Predicted WTP increased with survival benefits and respondents' income, regardless of how survival benefits were described. Framing therapeutic benefits as improvements in landmark rather than median time survival increased the proportion of the population willing to pay for that gain by 11–35%, and the mean WTP amount by 42–72% in the scenarios we compared.Conclusion : How survival benefits are described may influence the value people place on cancer care.